Inspection, Characterization and Classification of Defects for Improved CMP of III-V Materials. (1st January 2015) - Bhonsle, R. K.; Teugels, L.; Ibrahim, S. A. U.; Ong, P.; Delande, M.; Krishnan, S.; Siebert, M.; Struyf, H.; Leunissen, L. H. A.
Abstract : Understanding, characterizing and reducing defectivity after CMP is more critical than ever for future technology nodes <10 nm. III-V (e.g. InP and InGaAs) materials are of interest as high mobility channel materials for nMOS for achieving better device performance. In order to integrate these materials, one or more CMP steps are foreseen. Apart from improvement of roughness, we have found that there exist a range of defects on blanket wafers that need to be understood in order to optimize the polishing conditions and consumables. This paper will highlight a methodology to characterize and investigate the origin of defects. Further steps taken to minimize these defects are highlighted for 300 mm III-V wafers.